Challenges and strategies delivering group drama therapy via telemental health: Action research using inductive thematic analysis. Issue 2 (1st October 2020) - Wood, Laura L.; White, Savannah; Gervais, Danielle; Owen, Meghan; Moore, Sarah; Boylan, Zaira; Cosby, Olivia; Ansted, Jennifer; Capitman, Jamila; Ciempa, Travis; Dumar, Frances; Michel, Abby
When 'shelter in place' orders in Massachusetts went into effect during the COVID-19 pandemic, a dramatic increase occurred in the utilization of telemental health services, forcing clinicians to have to adapt their work online. This participatory action research (PAR) using inductive thematic analysis (ITA) explored challenges and recommendations in conducting group drama therapy via telehealth. Results included three broad themes: (1) technology literacy, (2) unique social justice dynamics and (3) translating drama therapy processes successfully online. Additionally, an overarching theme emerged that indicated drama therapy may be well suited to online group telemental health.